Analysis of Practicum Skills for Private High School Alumni in Bandung City in Higher Education - Tri Ayu Lestari; Baiq Sri Handayani (Postgraduate, University of Mataram, 2021)
This study aims to analyze the practical skills possessed by high school alumni to carry out practicum in higher education. The population in this study were high school alumni at universities. The sampling technique used is purposive sampling and snowball sampling. The subjects of this study were high school alumni who entered the faculties of Mathematics and Natural Sciences and Engineering, totaling 46 people. Data collection is done by using questionnaires and interviews. The results showed that as many as 69% of students found it difficult to carry out practical procedures, 43% of students found it difficult to follow biology practicum, and 59% of students found it difficult to use practicum tools. Based on these results, the benefits of the practicum that has been followed in high school on implementing practicum in lectures are a better understanding of the material, knowing how to use tools, and practicum in high school contributing when doing a practicum in lectures